2021
DOI: 10.1101/2021.04.13.439595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational modeling and quantitative physiology reveal central parameters for brassinosteroid-regulated early cell physiological processes linked to elongation growth of theArabidopsisroot

Abstract: Brassinosteroids (BR) are one of the key regulators of plant growth and development and have been the object of intense study. Whereas the individual components of the pathway have been well characterized experimentally, we employed computational modeling in combination with quantitative experiments to study the dynamics and regulation of the plasma membrane-localized fast BR response pathway in the epidermal cell layer along the Arabidopsis thaliana root axis that initiates early processes leading to cell elo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…The H + fluxes during the hydrotropic response were decreased especially in bri1-5 root elongation zone. Another study supported these observations by showing that triple or quadruple mutants in BRs receptor or co-receptors, including bri1, bak1, bri1brl1brl3, brl1brl3bak1 and bri1brl1brl3bak1, displayed reduced root growth and root curvature angles in the hydrotropism assay, while the BRL3 overexpression transgenic line demonstrated an increased root hydrotropic bending compared to wild type roots [59].…”
Section: Structural Characteristics Of the Pm H + -Atpasementioning
confidence: 81%
See 1 more Smart Citation
“…The H + fluxes during the hydrotropic response were decreased especially in bri1-5 root elongation zone. Another study supported these observations by showing that triple or quadruple mutants in BRs receptor or co-receptors, including bri1, bak1, bri1brl1brl3, brl1brl3bak1 and bri1brl1brl3bak1, displayed reduced root growth and root curvature angles in the hydrotropism assay, while the BRL3 overexpression transgenic line demonstrated an increased root hydrotropic bending compared to wild type roots [59].…”
Section: Structural Characteristics Of the Pm H + -Atpasementioning
confidence: 81%
“…Thus, low BR concentrations in the meristem and high in the root elongation zone contribute to the optimal root growth [57]. Interestingly, during root development the AHA2 transcripts are also increased in the transition and elongation zone, resulting in AHA2 protein accumulation and acidic apoplastic pH in the epidermal cells in this part of the root [59]. As BRI1 interacts directly with AHA2 and AHA7 [53][54][55][56], it was proposed that AHA2-containing-BRI1-BAK1 nanocluster at least in part regulates arabidopsis root growth along the root tip axis [59].…”
Section: Regulation Of Pm H + -Atpase Activity By Brsmentioning
confidence: 99%
“…The epidermis is widely described as the major site for BR-promoted gene expression in the root (Chaiwanon and Wang, 2015; Fridman et al, 2014, 2021; Großeholz et al, 2021; Hacham et al, 2011; Nolan et al, 2020; Vragović et al, 2015; Wei and Li, 2016). Previous studies showed that epidermal expression of BRI1 was sufficient to rescue morphological phenotypes including meristem size and root length of loss-of-function BR mutants such as bri1-T (Fridman et al, 2014; Hacham et al, 2011; Kang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical modelling complements phenotyping advances by overcoming the challenges of experimental approaches and benefits from the emerging field of functional phenomics (York, 2019). Highlights from the diversity of modelling approaches presented at ISRR/Rooting2021, in both spatial and temporal scales, include: a micro‐hydrological model that describes a new symplastic water pumping mechanism (Couvreur et al ., 2021); the dynamics and regulation of a fast brassinosteroid response pathway in Arabidopsis root tips (Großeholz et al ., 2021); functional–structural plant (FSP) models to identify optimal root phenotypes for nutrient capture in contrasting environments (Rangarajan, 2021); and field‐scale simulations of plant populations and communities (Postma et al ., 2017; Schnepf et al ., 2018; Faverjon et al ., 2019). Future mathematical models will draw on larger, more complex, datasets incorporating novel imaging technology, high‐throughput phenotyping and availability of relevant environmental data.…”
Section: Unleashing the Power Of Mathematical Modellingmentioning
confidence: 99%